(untitled) (Quinto Sol, 2012)
The colonization process that began in Santa Fe province in the mid of the nineteenth century radically transformed its productive structure. The settlement of agrarian colonies of European immigrants in borderlands helped to the emergency of an active real state market supplied not only by the immigration demand, but also from a continuous offer of new lands and the emergence of a broad spectrum of businessmen and entrepreneurs that would specialize in colonization. Therefore this article expects to analyze the two first decades of the land market which emerged from that newly productive configuration in the most important colonies of the province, Esperanza and San Carlos. We will try to examine the changes of this market and the economic impact that this process produced in the provincial economic system. From a survey of all land sales in these colonies during the chosen period, we will attempt to show the progression in land prices, the differences according to the surface of productive units, the ways of payment and financing and the rotation speed of plots between owners.